A survey on how students seek information on the internet - Krausz-Princz, Mária (Teaching Mathematics and Computer Science, 2006)
Navigating among the information available on the Internet has become an expectation for the members of the information society we are living in. This especially applies to students of higher education, the intellectuals of the future. It is a general experience that most users make one or two word searches and they don’t know about the possibilities offered by various search engines, which can make searches more effective. Given results from abroad we have set up a study among the students of the University of Debrecen (UD) about their use of the Internet, their knowledge of searching strategies and techniques, their perceptions of the effectiveness and efficiency of search engines. This paper reports the results of this study. The results imply that it is imperative that area should be included in the curriculum.